A review of Pedro Rodrigo Sabalette about polio (1948) - Francisco Herrera Rodríguez (Universidad de Alicante, 2015)
Although Pedro Rodrigo Sabalette (1904-1947) was an important personality in the Spanish Medicine in the first third of the 20th century, nowadays he is a forgotten figure. As he died in his youth, he was not able to develop the best of his clinical, teaching and researching aspects. He contributed to the Manual de Patología Médica, edited by Misael Bañuelos, in which he wrote the chapter on diseases of the central and peripheral nervous system; one of those items was about poliomyelitis. We have used in our study the sixth edition of the mentioned Manual, published in 1948 when Rodrigo Sabalete was already dead. Those pages on poliomyelitis are a source of great interest to know what the knowledge of that disease was in the late 1940's in aspects such as: etiological, pathogenic, clinical-anatomopathological, prophylactic and therapeutic.